Performance of maize genotypes of Rio Grande do Sul using mixed models - Baretta, Diego; Nardino, Maicon; Carvalho, Ivan Ricardo; Oliveira, Antonio Costa de; Souza, Velci Queiróz de; Maia, Luciano Carlos da (Científica, 2016)
The initial process for genetic gain in maize is obtained by identifying sources of variability in open pollinated populations. For the evaluation of these populations, statistical procedures as REML/BLUP analysis, has been increasingly employed by maize breeders. This study aimed to use the method of mixed models (REML / BLUP) for the estimation of genetic parameters and evaluation to a set of agronomic characters in hybrid genotypes, synthetic and landraces and verify its potential for breeding purposes and/or indicate their crop for small farmers in the Pelotas region. The characters evaluated were: tassel length (TL), tassel branch number (TBN), ear insertion height (EI), grain yield (GY), ear row number (ERN), kernels per row (KPR) and weight of a hundred grains (WHG). Were estimated by the mixed models of variance components by restricted maximum likelihood (REML) and the components of the prediction of the average, best linear predictor unbiased (BLUP). The best genotypes which presented final genotypic values superior to the general mean were the double hybrid COODETEC 308 for the characters TL, TBN, EI, GY and ERN; the single hybrid AS1551, triple hybrid AS3466 and synthetic BRS Planalto for TBN, EH, GY and ERN. Also, the populations Caiano Branco for TL, ERN and EI; Caiano Rajado for GY and ERN; Criolão for TBN and WHF; Dente de ouro for TL and ERN; Branco Roxo Indio for TL and WHG and Argentino Branco for TL and TBN. The genotypes BRS Planalto and Caiano Rajado show grain yield above the overall average and show promise for use by small and breeding programs.